15.6k views
3 votes
Write two linear functions, (x) and g(x). For example, f(x) = 3x - 7 and

g(x) = -2x + 5. Then see whether Rx) - (-9(x)) is equivalent to f(x)+ g(x). Hint:
To find -9(x), just change the signs of all the terms in g(x). Discuss whether
you think your results would apply to every function.

Write two linear functions, (x) and g(x). For example, f(x) = 3x - 7 and g(x) = -2x-example-1
User LPH
by
5.7k points

2 Answers

3 votes

Answer:

And the results would apply to every fonction.

Write two linear functions, (x) and g(x). For example, f(x) = 3x - 7 and g(x) = -2x-example-1
User Sten Petrov
by
6.5k points
3 votes

Answer:


f(x)-(-g(x)) is equivalent to
f(x)+g(x).

Explanation:

Given : Functions
f(x)=3x-7 and
g(x)=-2x+5

To find :
f(x)-(-g(x)) is equivalent to
f(x)+g(x) ?

Solution :


f(x)=3x-7


g(x)=-2x+5


-g(x)=-(-2x+5)=2x-5

First we determine,


f(x)+g(x)=3x-7+(-2x+5)


f(x)+g(x)=3x-7-2x+5


f(x)+g(x)=x-2

Now, we find


f(x)-(-g(x))=3x-7-(2x-5)


f(x)-(-g(x))=3x-7-2x+5


f(x)-(-g(x))=x-2

So,
f(x)-(-g(x)) is equivalent to
f(x)+g(x).

User Binara Thambugala
by
6.1k points